Two neuropeptide signaling pathways regulate post-mating refractoriness and reproductive system in male crickets - Zhen Zhu; Shinji Nagata (Communications Biology)
Abstract After mating, some insects drastically reduce mating activity, termed post-mating refractoriness, due to physiological restrictions. Male crickets, Gryllus bimaculatus, characteristically exhibit a 1-hour post-mating refractory stage, which is controlled by terminal abdominal ganglion. The molecular mechanisms underlying the male-specific precisely timed refractory stage remain unclear. Here, we show that among 28 neuropeptide precursors expressed in the terminal abdominal ganglion, myosuppressin, allatotropin, and sNPF exhibited male-specific expression based on RT-qPCR and in situ hybridization. RNA interference experiments showed that only the knockdown of allatotropin and sNPF extended the refractoriness duration. Furthermore, allatotropin and sNPF knockdown influenced the male reproductive system by inhibiting seminal fluid secretion from the male accessory gland and decreasing spermatozoon storage in seminal vesicles, respectively. Knockdown of allatotropin and sNPF receptors caused similar phenotypes to their ligands. In conclusion, this study demonstrated the regulation of post-mating refractoriness and reproductive system by Allatotropin and sNPF signaling pathways in male crickets.